Arquitetura SCADA para sistemas de geração distribuída baseada em gateway para comunicação DNP3 segura - Figueiredo, Hugo Fernando Magalhães de (2021)
SCADA systems applied to power generation have undergone several updates over the years. Mainly in sectors related to communication networks, which motivates researchers to raise their attention to resources that can provide security to these systems. Therefore, this work seeks to increase the security of a SCADA Smart Grid system by applying a secure communication gateway based on the TLS protocol. The proposed gateway can provide additional protection to a SCADA Smart Grid system composed of the DNP3 protocol since most of the supervisory systems used today do not support data security coming from communication networks. With this configuration, the gateway is on the utility distribution company network. Thus, the utility's SCADA system and the energy managers controlled by it connect to the gateway. This approach reduces the possibility of attacks and provides a simple connection of managers on user networks, which do not have an accessible external IP. Finally, in this proposal, unsecured communication is restricted to a local connection and protected in other ways. The security tests were implemented by a plug-in developed for the Ettercap software. The experimental results prove the eficiency of the proposed system in preventing Man-In-The-Middle attacks.